Dekret o rejestracji i zakazie wywozu dzieł sztuki z 1946 roku – czy praktyka rozmijała się z celami regulacji prawnej? - Szafrański, Wojciech (Studia Iuridica Toruniensia, 2013)
<!--[if gte mso 9]> <![endif]--> The implementation of the decree dated March 1, 1946 on the registration and banning the export of works of art in Poland seems to have been a complete oddity. It remains open for debate whether the decree was prepared due to the need of the moment or rather was part of an elaborate plan to take over objects of exceptional class by the state and to provide the state with a means to control all privately-owned works of art, which would be the fi rst step in completely eliminating the circulation of antique works that remained beyond the control of the state. The implicit cause for adopting the decree was an event that took place during the war, when Alfred Potocki removed part of his collection from the Łańcut Castle, and the subsequent attempt to export the collections of Krzeszowice and Łańcut. In practice, however, the regulations on obligatory registration were not enforced in the slightest in 1946, proof of which is the fact that no case of registration has ever been recorded, although it is beyond any doubt that works of art were being traded at the time, and even prominent party members and high-ranking off icials were already gathering works of art and object that were subject to registration as early as in 1945. It was similar when it comes to illegal moving of objects abroad. Out of all disclosed cases only one took place in 1946 after the publication of the decree and at the same time it became the touchstone for the regulations introduced in March of that year, and led to a show trial dealing with “antique smuggling”. It would be naive to state that the political decisionmakers believed in the causative power of the new regulations or that they expected a wave of work of art registration applications to follow. The number of such applications, both from private owners as well as institutions and art traders, was less than modest all the way until the 1950s. The threat of penal sanctions under the decree changed little in this matter, although it did give the authorities a mechanism that might have served as a deterrent for private collectors or generally the citizens who owned any family heirlooms or historical relics. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->